Contrasting mixed siliciclastic-carbonate shelf-derived gravity-driven systems in compressional intra-slope basins (southern Hikurangi margin, New Zealand). (December 2021) - Claussmann, B.; Bailleul, J.; Chanier, F.; Caron, V.; McArthur, A.D.; Mahieux, G.; Chaptal, C.; Vendeville, B.C.
Abstract: Along active margins, the combination of predominant tectonic activity and shallow-marine mixed siliciclastic-carbonate source systems developing upon and around actively growing structures challenges traditional source-to-sink models. This study aims to investigate the implications of mixed siliciclastic-carbonate shelfal domains located in contrasting geotectonic settings (thrust forelimb and backlimb) for the development of the concomitant gravity-driven systems beyond the shelf edges. Here, we document the vertical and lateral stratigraphic variabilities of the shelf-derived turbidites and mass-transport deposits (MTDs) at outcrop-scale through the integrated interpretation of photogrammetry, field and taphonomic data from the emerged southern portion of the Hikurangi subduction margin. Results highlight the role and importance of varying structural setting of the sediment source, whereby the different morphologies of the source regions (continent-attached forelimb, continent-detached backlimb) control the development of highly varied shelf-derived gravity-driven depositional systems that interact with the structures across the same confined intra-slope basin. The deposits are tens to a few hundred of meters in thickness and have a lateral extent of several kilometers. The depositional systems are characterized by durations of 1 to 2 Ma and were primarily controlled by the geometries and tectonic motion of the underlying structures at the shelf edges. Shelf-derived mass-wasting systems occurred on both sides of the actively growing thrust structures and were sourced from both shelfal domains that were attached or detached from the continental domain. When sourced from the backlimbs however, the subsequent MTDs exhibit more complex internal architectures, ultimately recording the dynamic changes in slope gradient, and can therefore be used as proxies for unraveling the tectonic activity of an individual structure. Our study provides new insights to better predict mixed siliciclastic-carbonate depositional settings along active margins, sourced from thrust forelimb and backlimb. These results may be important for deep-marine exploration and tectonostratigraphic reconstruction of fold-and-thrust belts. Highlights: Geometry and tectonic motion of the underlying structures at the shelf edges chiefly control mixed gravity-driven systems. Shelf-derived mass-wasting events can occur on both sides of actively growing asymmetrical structures (thrusts). MTDs can either be sourced from shelfal domains that are attached to the main continental domain or detached from it. MTDs from thrust backlimb can exhibit more complex architectures ultimately recording the dynamic changes in slope gradient. MTDs can be used as proxies for unraveling the tectonic activity of an individual structure